Influência da composição da mistura reacional no desempenho de catalisadores NiFe/MgAl2O4 em reações de reforma - Lara, Thais Paula Nogueira (2021)
This thesis evaluated the application of Ni-, Fe- and Ni-Fe/MgAl2O4 catalysts in Ethanol Steam Reforming (ESR), Ethanol Steam Reforming with hydrogen gas (ESRH), Methane Dry Reforming (RSM), Methane Steam Reforming (RVM) and Methane Bi-Reforming (BRM) reactions evaluating the influence of reaction medium composition and Ni:Fe ratio on the catalytic behavior. Two series of NiFe/MgAl2O4 catalysts were prepared, the first keeping the Ni content at 8 wt.% and varying the Fe content, and the second keeping the total metallic content fixed at 15 wt.%. The properties of the catalysts were investigated by X-ray diffraction, N2 physisorption and temperature-programmed reduction. The characterizations showed the formation of high purity support with high surface area. Although the iron catalyst had low activity in methane reforms, the Ni and NiFe catalysts were active in these reactions. The addition of iron increased the conversion of methane on RVM, indicating the iron-promoter character on this reaction. Ethanol catalytic tests were carried out under ESR conditions (H2O/C2H6O ratio equal to 3) and in ESRH (ESR strongly reduced by the addition of H2) between 250 and 650 °C. In situ XRD and in situ XANES analyzes were performed during the reduction in H2 and in the ESR and ESRH reactions to evaluate the catalyst dynamics under these conditions. The addition of iron reduced methane production and carbon deposition, increasing stability in ESR. The bimetallic catalysts formed the NiFe2O4 phase which, when reduced, formed the NiFe alloy. When the catalysts were placed in contact with the ESR reagents, partial oxidation of nickel and iron particles occurred at low temperatures, reducing the catalytic activity. As the temperature increased, nickel particles reduced and activity increased. Iron particles were more susceptible to oxidation, migrating to the surface in the form of oxides and partially segregating from the alloy. This small oxidation favored the catalytic stability by reducing the carbon production compared to the catalyst that contained only nickel. The intensity of this process depends on the composition of the reactants and catalysts. In ESRH, the oxidation process of the particles was milder, stabilizing the catalyst structure and increasing the activity at low temperatures. In this way, it was possible to evaluate that the composition of the reaction medium and the metallic charge influenced the catalytic performance.